2015
DOI: 10.1098/rspb.2014.2395
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ( ApoE ) polymorphism is related to differences in potential fertility in women: a case of antagonistic pleiotropy?

Abstract: The alleles that are detrimental to health, especially in older age, are thought to persist in populations because they also confer some benefits for individuals (through antagonistic pleiotropy). The ApoE4 allele at the ApoE locus, encoding apolipoprotein E (ApoE), significantly increases risk of poor health, and yet it is present in many populations at relatively high frequencies. Why has it not been replaced by natural selection with the health-beneficial ApoE3 allele? ApoE is a major supplier of cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 73 publications
1
36
0
2
Order By: Relevance
“…Our observations on APOE ε4 and fertility extends findings from rural Ecuador, where APOE ε4 carrying women had more offspring [31]· Moreover, young regularly menstruating women with APOE ε4 in rural and urban Poland have higher levels of progesterone in the luteal phase, suggesting a higher fecundability [32]. However, the findings from these two studies are based on relatively small samples.…”
Section: Discussionsupporting
confidence: 79%
“…Our observations on APOE ε4 and fertility extends findings from rural Ecuador, where APOE ε4 carrying women had more offspring [31]· Moreover, young regularly menstruating women with APOE ε4 in rural and urban Poland have higher levels of progesterone in the luteal phase, suggesting a higher fecundability [32]. However, the findings from these two studies are based on relatively small samples.…”
Section: Discussionsupporting
confidence: 79%
“…The persistence of APOE4 in modern populations, despite its later costs to lifespan and brain aging, may be due to benefits to young ages. APOE4 women have higher luteal phase blood progesterone (Jasienska et al, 2015), which may enhance fertility. Moreover, APOE4 may be adaptive in immunity by higher cytokine responses (Finch and Morgan, 2007) and in pathogen resistance (Azevedo et al 2014; Finch and Martin, 2015; Rougeron et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving a population with modern reproductive patterns, however, the APOE e4 allele, a recognized risk allele for Alzheimer's disease and cardiovascular disease which prevents the attainment of advanced age 37 , was found to be associated with reduced fertility 40 , showing a negative pleiotropic action on both survival and fertility in modern populations. A more recent study has suggested that it may predispose to higher fertility 41 .…”
Section: Rejuvenation Researchmentioning
confidence: 98%